Persiapan Praktek Implementasi Bahan Ajar IPA Berbasis TPACK di Malaysia - Hariyono, Eko; Erman; Indana, Sifak; Sukarmin (Universitas Muhammadiyah Prof. DR. Hamka (UHAMKA Press), 2024)
Background: Considering the significant impact of Technological Knowledge (TK), Content Knowledge (CK), and Pedagogical Knowledge (PK) modeling on teachers' ability to improve quality learning, practical preparation in the form of training for science teachers aims to prepare the application of TPACK quality in more effective learning. This effort is also a form of support for Indonesia-Malaysia cooperation in implementing internationalization programs. Method: Through the steps of needs analysis, planning, implementation, and evaluation, these findings reveal that Malaysian SIKL teachers have a good understanding of TPACK after the implementation of the training. It can be seen from the learning tools that have been developed that they have integrated TPACK in the learning tools, although they still need to be improved. Result: Especially in the aspect of teachers not being optimal in following developments in learning technology. Conclusion: The evaluation notes from this research provide recommendations for future research to promote sustainable teacher training programs to truly be able to create appropriate TPACK-based learning demands in the 21st century era.